84.6k views
1 vote
Help asap please!! I don’t understand

Help asap please!! I don’t understand-example-1
User CppChase
by
5.7k points

1 Answer

3 votes

Answer: 2+
(6x-2)/(x(x-3)) ==> x
\\eq0, x
\\eq3

Explanation:

f(x)=2x^2-2

g(x)=x^2-3x

(f/g)(x)=


(2x^2-2)/(x^2-3x)=


(2x^2-6x+6x-2)/(x^2-3x)=


(2x^2-6x+6x-2)/(x^2-3x)=

2+
(6x-2)/(x^2-3x)=2+
(6x-2)/(x(x-3)) ==> x
\\eq0, x
\\eq3

User Rogerstone
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.